Pemanfaatan Teknologi High Volume Fly Ash Concrete Untuk Memproduksi Beton Kuat Tekan Normal - Sari, Neni Anggoro, Mochamad Solikin, S.T., M.T., Ph.D, Yenny Nurchasanah, S.T., M.T (2016)
Concrete technology has developed very rapidly, so concrete supporting materials wich able to modify the properties and characteristics of the concrete in order to facilitate the work or energy saving are needed. The use of fly ash as a fine powder added material to replace cement up to 50% (high volume fly ash) was striving to be used as a useful material. This research was conducted by examining the development of compressive strength of normal concrete, high volume fly ash concrete with the addition of chemicals superplasticizer as much as 1% by using low fas at 14 days, 28 days, 56 days and testing the value of water absorption of concrete on 56 days. The result of reviews of mpressive strength for normal concrete, HVFA concrete and HVFA-SP concrete at 14 days respectively was 18,109 MPa 9,620 MPa and 4,716 MPa, at 28 days respectively was 19,241 MPa 10,186 MPa and 8,300 MPa, at 56 days respectively was 19,618 MPa 16,600 MPa and 12,450 MPa. The test result of water absorption concrete at 56 days each were 7,832% 7,597% and 6,745%. The compressive strength of high volume fly ash concrete decreased than the compressive strength of normal concrete, fine powder of fly ash as a concrete additive can be tested in the field by conducting further studies to obtain the compressive strength of concrete optimally. Concrete water absorption value of high volume fly ash concrete was smaller than normal concrete, this was very good because it can prevent cracks smooth concrete surface.